Stunting and PMT counseling dissemination in Argomulyo Village, Cangkringan District - Eko Nugroho; Iswanto Suwarno; Nia Maharani Raharja; Ahmad Syarif Edi Nugroho; Annisa' Viesta Yustitia Arini; Gál Bence; Tzenko D. Vatchev (Peneliti Teknologi Teknik Indonesia, 2023)
Argomulyo Village, which is in the administrative area of Kapanewon Cangkringan, is one of the areas with a relatively low level of sensitivity to children's health. The purpose of this community service is to increase the sensitivity of the community, especially mothers of toddlers to children's health. The methods used include surveys, providing information to the padukuhan, preparation stage, stunting counseling process, giving PMT. This activity aims to raise awareness, provide or increase knowledge and attitudes. Community service activities in the Argomulyo Village generate new knowledge for mothers of toddlers so they can minimize the possibility of stunting in children. This knowledge can then be conveyed in the POSYANDU forum in each hamlet so that it benefits the surrounding community.